PRODUKSI DAN KARAKTERISTIK GELATIN HALAL BERBAHAN DASAR USUS AYAM - Jajang Gumilar dan Andri Pratama (Jurnal Teknologi Industri Pertanian, 2018)
Gelatine is one of the most indispensable products in the food industry, pharmaceutical industry, photography industry, and other industries. Currently, the demand for gelatine in Indonesia is almost 100% fulfilled by gelatine imports from various countries. Imported gelatineare obtained from the hydrolysis of collagen from pigs and cattle body parts, which causes the anxiety of the Indonesian because the majority of Indonesian are moslems. Moslems forbid all types of food products derived from pigs and livestock that are not slaughtered using Islamic ways. Therefore, it is necessary to find out various raw materials alternatives to get halal gelatine. Gelatine can be made from various body tissues of livestock such as chicken intestines. The main ingredients of the intestine are proteins including collagen. Gelatine is obtained from collagen hydrolysis. Optimization of the acid concentration and soaking time at the demineralization stage influence to gelatine quality. This experiment was conducted experimentally, the design used was a complete randomized design with factorial pattern, the treatments were hydrochloric acid concentration (3, 5, and 7%) and soaking time (24, 48, and 72 hours), each treatment was repeated four times. Variant analysis was used to determine the treatment difference, followed by Duncan’s Multiple Range Test (DMRT) to test the differences between treatments. The results showed that there was an interaction between the use of hydrochloric acid concentration with the length of soaking time on the quality of chicken intestine gelatine. The use of 3% hydrochloric acid with 24 hours soaking time resulted the best quality of chicken intestine gelatin, and had gelatine characteristic ie yield of 4.33%; water content of 5.49%; ash content 3.80%; pH 5.5; and gel strength of 157.48 g bloom.Keywords: gelatin, characterization, production, chicken intestine